Analysing the Impact of Smart City Networks in Telecommunications Regulation and Standardization: the Spanish Case - Álvaro Palomo-Navarro; Julio Navío-Marco; Maria Luisa Martínez-Cespedes; Olga Gil (International Telecommunications Society (ITS), 2016)
Since its establishment in 2011, the Spanish Network of Smart Cities (RECI) has worked towards the ultimate objective of making Spanish cities an international reference within the global `smart' panorama. This network, originally empowered by the individual experience of many Spanish cities with presence in international smart city projects for over 10 years, has adopted a powerful governance structure, including its own particular network coordination and management mechanisms. Overall, this environment can be considered a fast track to learning in matters of smart cities governance and project implementation and a powerful tool for collaborating with the remaining stakeholders. The final objective of this work focuses on providing a full picture of the impact of RECI on the Spanish smart cities and its influence in policy-making and standardization. The conclusions of this study show the important role that RECI has played in the recent development of Spain as an international reference in the field of smart cities. It also shows a positive correlation between RECIs influence on government and normalisation bodies to guarantee the success of RECIs participant strategies.
Keywords: 330